2020
DOI: 10.1111/jcmm.15187
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin promotes the neuronal differentiation of bone marrow mesenchymal stem cells in vitro and in vivo: Involvement of Nrf2 signalling pathway

Abstract: Bone marrow mesenchymal stem cell (BMSC) transplantation represents a promising repair strategy following spinal cord injury (SCI), although the therapeutic effects are minimal due to their limited neural differentiation potential. Polydatin (PD), a key component of the Chinese herb Polygonum cuspidatum, exerts significant neuroprotective effects in various central nervous system disorders and protects BMSCs against oxidative injury. However, the effect of PD on the neuronal differentiation of BMSCs, and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The model of SCI was induced under sterile conditions and performed according to Allen’s method as previously described [ 23 ]. Before surgery, the mice were anesthetized using 1% pentobarbital sodium (50 mg/kg) by intraperitoneal injection (i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The model of SCI was induced under sterile conditions and performed according to Allen’s method as previously described [ 23 ]. Before surgery, the mice were anesthetized using 1% pentobarbital sodium (50 mg/kg) by intraperitoneal injection (i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), which are easy to obtain, ethically uncomplicated, and relatively safe, have emerged as a promising candidate for SCI treatment, with the potential to differentiate into neuron‐like cells. Although this approach remains controversial, experimental evidence has suggested that MSCs, after suitable modifications, can display phenotypic and functional neuronal properties 6,7 . We have previously reported that an MSC‐derived neural network (MN) implantation strategy was able to facilitate the recovery of limb motor function in a rat model following thorough spinal cord transection 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different stem cell sources available, MSC is an abundant source of immature immune cells, with no ethical concerns [14,25]. They can be easily acquired, maintained, expanded quickly, and differentiated into neural cell types in vitro and in vivo [26,27]. No invasive procedures are required to obtain bone marrow-derived MSCs, and it has been safely used clinically.…”
Section: Discussionmentioning
confidence: 99%